Estrogens Regulate the Hepatic Effects of Growth Hormone, a Hormonal Interplay with Multiple Fates - Fernandez-Perez, Leandro; Borja-Guerra, Carlos; Diaz-Chico, Juan Carlos; Flores-Morales, Amilcar (Frontiers in Endocrinology, 2013)
The liver responds to estrogens and growth hormone (GH) which are critical regulators of body growth, gender-related hepatic functions, and intermediate metabolism. The effects of estrogens on liver can be direct, through the direct actions of hepatic ER, or indirect, which include the crosstalk with endocrine, metabolic, and sex-differentiated functions of GH. Most previous studies have been focused on the influence of estrogens on pituitary GH secretion, which has a great impact on hepatic transcriptional regulation. However, there is strong evidence that estrogens can influence the GH-regulated endocrine and metabolic functions in the human liver by acting at the level of GHR-STAT5 signaling pathway. This crosstalk is relevant because the widespread exposition of estrogen or estrogen-related compounds in human. Therefore, GH or estrogen signaling deficiency as well as the influence of estrogens on GH biology can cause a dramatic impact in liver physiology during mammalian development and in adulthood. In this review, we will summarize the current status of the influence of estrogen on GH actions in liver. A better understanding of estrogen-GH interplay in liver will lead to improved therapy of children with growth disorders and of adults with GH deficiency.